Crowdfunding Platforms Under Turkish Capital Market Law With a Special Reference to Investment Committee - Akin, Nesrín (Revista Amagis Jurídica, 2024)
Crowdfunding is increasingly an established form of alternative finance for start-ups and SMEs, relying on small investments. Crowdfunding represents an important type of intermediation where a crowdfunding platform operates a digital platform open to the public in order to match or facilitate the matching of prospective investors or lenders with businesses that seek funding. It is compulsory to form investment committee by the Board of Directors of the platform under Turkish Capital Market Law. Investment committee assesses the feasibility and creditworthiness assessment reports issued about project belonging to entrepreneur or venture capital firm and approves the crowdfunding information form prepared about campaigns.